Development of Swimming Learning Media to Improve the Understanding of Elementary School Students - N Dian Rahmawati; Encep Sudirjo; Anggi Setia Lengkana; Rizal Ahmad Fauzi (Universitas Tadulako, 2026)
This research aims to develop digital learning media based on the RENANGKU application as an innovation in physical education learning media to introduce swimming sports material and improve the cognitive understanding of elementary school students. The method used in this research is Research and Development (R&D) with a 4D development model which includes the define, design, development, and disseminate stages. In the development process, the media was designed using the Canva application and continued with Smart Apps Creator to produce learning media that is interactive, structured, and suited to the characteristics of elementary school students. The suitability of the learning media was tested through a validation process by material experts, language experts, and media experts. The validation results showed a very good level of suitability, namely 96% from material experts, 98% from language experts, and 84% from media experts, so that the media was declared very suitable for use in learning. Furthermore, trials were conducted in small groups and large groups with feasibility percentages of 85% and 89.8%, respectively. The large-group trial involved 25 elementary school students. The results of media implementation showed an increase in students' cognitive understanding, which can be seen from the improvement in the average score from 74.93% to 77.92%. Based on these findings, the RENANGKU digital learning media has been proven to be feasible, practical, and effective as an alternative physical education learning media for swimming material in elementary schools.